Discriminating between models of ambiguity attitude: A qualitative test - Robin Cubitt; Gijs van de Kuilen; Sujoy Mukerji (Queen Mary University of London, School of Economics and Finance, 2017)
During recent decades, many new models have emerged in pure and applied economic theory according between Epstein (2010) and Klibanoff et al. (2012) identified a notable behavioral issue that distinguishes sharply between two classes of models of ambiguity sensitivity that are importantly different. The two classes are exemplified by the -MEU model and the smooth ambiguity model, respectively; and the issue is whether or not a desire to hedge independently resolving ambiguities contributes to an ambiguity averse preference for a randomized act. Building on this insight, we implement an experiment whose design provides a qualitative test that discriminates between the two classes of models. Among subjects identified as ambiguity sensitive, we find greater support for the class exemplified by the smooth ambiguity model; the relative support is stronger among subjects identified as ambiguity averse. This finding has implications for applications which rely on specific models of ambiguity preference.
Keywords: C91; D01; D03; D81; G02; 330; Ambiguity sensitivity; ambiguity attitude; testing models of ambiguity sensitive preference